2015
DOI: 10.1186/s12889-015-1544-5
|View full text |Cite
|
Sign up to set email alerts
|

Number of visits to the emergency department and risk of suicide: a population- based case–control study

Abstract: BackgroundThe aim was to study whether number of visits to emergency department (ED) is associated with suicide, taking into consideration known risk factors.MethodsThis is a population-based case–control study nested in a cohort. Computerized database on attendees to ED (during 2002–2008) was record linked to nation-wide death registry to identify 152 cases, and randomly selected 1520 controls. The study was confined to patients attending the ED, who were subsequently discharged, and not admitted to hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…One interpretation of this finding is that mental health diagnosis is associated with a higher number of emergency department visits, which others have similarly described. 6,10,21 A recent case-control study nested in the cohort of patients presenting to the emergency department in Reykjavik, Iceland found that suicide risk increased with the number of ED visits in a dose-response matter even after controlling for age, gender and psychiatric diagnoses. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One interpretation of this finding is that mental health diagnosis is associated with a higher number of emergency department visits, which others have similarly described. 6,10,21 A recent case-control study nested in the cohort of patients presenting to the emergency department in Reykjavik, Iceland found that suicide risk increased with the number of ED visits in a dose-response matter even after controlling for age, gender and psychiatric diagnoses. 10 …”
Section: Discussionmentioning
confidence: 99%
“…A handful of case-control studies comparing patterns of healthcare utilization between suicide cases and members of the general population have been conducted in Canada, 6,7 Taiwan, 8 the United Kingdom, 9 Iceland 10 and Denmark 11 as well as among U.S. military service members 12 and on an Indian reservation in the upper Midwest. 13 These studies largely focus on specific types of visits rather than overall patterns of healthcare use; for example, outpatient visits to general practitioners and/or mental health providers, 7–9,12 emergency department visits 10 or inpatient hospitalizations. 11 Only one compares patterns of healthcare utilization in outpatient, inpatient, emergency and community mental health settings among adults in Alberta, Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency departments (EDs) are a key setting for suicide prevention, as up to 8% of all ED patients have active or recent suicidal ideation (SI), [4-6] multiple ED visits appear to be a risk factor for suicide, [7] and many suicide victims are seen in an ED shortly before death. [8] Based on models using national suicide statistics, ED-based interventions might help decrease suicide deaths by 20% annually.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Reducing access to firearms (e.g., through locked storage at home or through storage out of the home) is particularly important, since firearm suicide attempts (SAs) have a high case-fatality rate and firearms account for 51% of all suicide deaths in the United States. [3] Emergency departments (EDs) are a key setting for suicide prevention, as up to 8% of all ED patients have active or recent suicidal ideation (SI), [4][5][6] multiple ED visits appear to be a risk factor for suicide, [7] and many suicide victims are seen in an ED shortly before death. [8] Based on models using national suicide statistics, EDbased interventions might help decrease suicide deaths by 20% annually.…”
Section: Introductionmentioning
confidence: 99%